Hypocholesterolemic activity of Monascus fermented product in the absence of monacolins with partial purification for functional food applications - Ajdari, Zahra; Abd Ghani, Maaruf; Ayob, Mohd Khan; Bayat, Saadi; Mokhtar, Mazlin; Abbasiliasi, Sahar; Khoramnia, Anahita; Rahman, Heshu Sulaiman; Mehrbod, Parvaneh; Ajdari, Daniel; Ariff, Arbakariya (Hindawi Publishing Corporation, 2014)
Hypercholesterolemia is one of the most common chronic diseases in human. Along with chemical therapy traditional medication is used as hypocholesterolemic remedy, however, with unfavorable side effects. Recently, Monascus fermented product (MFP) has become a popular hypocholesterolemic natural supplement. In the present study, the hypocholesterolemic activity of Monascus purpureus FTC5391 fermented product ethanolic extract (MFPe) was investigated in hypercholesterolemic rats. Results showed that MFPe not only reduced the serum total cholesterol (TC), LDL-C, TG concentration, and TC/HDL-C ratio but also increased the HDL-C. Further, solid phase extraction (SPE) was carried out to obtain the hypocholesterolemic bioactive fraction. The high polar fraction of SPE increased the HDL-C (42%) and decreased the TC (53.3%), LDL-C (47%), and TG (50.7%) levels as well as TC/HDL-C ratio (69.1%) in serum. The GC-MS results of the active fraction revealed two main compounds, isosorbide and erythritol, which act as coronary vasodilator compounds.